Hostility and the clinical course of outpatients with congestive heart failure. Issue 2 (1st February 2016) - Rafanelli, Chiara; Gostoli, Sara; Tully, Phillip J.; Roncuzzi, Renzo
Abstract : Objective: The role of depression and quality of life on clinical outcomes of congestive heart failure (CHF) is well recognised. However, there are fewer studies investigating the prognostic role of subclinical psychological distress and well-being impairments. The aims of this study were to evaluate clinical/subclinical psychological distress and well-being in CHF outpatients, and the influence of these psychological factors on adverse cardiac events (re-hospitalisation, cardiac death), at 4-year follow-up. Design: Sixty-eight CHF outpatients underwent psychological assessment at baseline and, after 4 years, information about cardiac events was collected in 60 patients by means of clinical records. Main outcome measures: Psychological assessment included structured clinical interview for DSM (major/minor depression), Interview for diagnostic criteria for psychosomatic research (demoralisation), symptom questionnaire, psychological well-being scales. Results: At follow-up, 39.7% of the baseline sample reported cardiovascular events (14 CHF-related re-hospitalisations and 13 cardiac deaths) and 5.9% other causes for death. Among the variables examined as potential risk factors for adverse cardiovascular outcomes, only hostility was significant, even after controlling for disease severity (hazard ratio = 2.38, 95%confidence interval: 1.04–5.45, p = .040). Conclusion: In outpatients with CHF, psychological assessment should include both clinical and subclinical distress such as hostility, in order to better address psychological risk factors for cardiac outcomes.